Disparities in Glycemic Outcomes Persist in Youth with Type 1 Diabetes and High-Technology Use - Nath, Meryl C.; Frey, Blake; Atchison, Joycelyn; Schmitt, Jessica A. (Pediatric diabetes, 2023)
Background. Racial disparities are well described in glycemic outcomes in youth with Type 1 diabetes mellites (T1D). Hemoglobin A1c (HbA1c) has some limitations in comparing glycemia across patient groups as there are individual variations in mean glucose and HbA1c. Objective. This study aimed to compare glycemic metrics obtained from (Dexcom G6) continuous glucose monitor (CGM) device with HbA1c levels controlling for race, age, duration of diabetes, race, insurance status, and insulin pump use with glycemic control. Subjects and Methods. Data analyzed included 188 patients, majority non-Hispanic White (NHW) (n = 147, 78.2%) and majority privately insured (n = 147, 78.2%). Half of the patients were using insulin pumps, (n = 94, 50.0%) and approximately half were female. Median age was 16.6 (interquartile range: 14.2–18.2) years old with a median age of diabetes diagnosis at 9.3-years old. Results. Significant differences were observed between NHW and non-Hispanic Black (NHB) patients in terms of HbA1c, 90-day mean glucose, and 90-day time >250 mg/dL (>13.9 mmol/L) (7.6% vs. 9.2%, 181 mg/dL vs. 220 mg/dL, and 16.3% vs. 34.7%, respectively, p<0.001 for all comparisons). Multiple linear regression analysis was performed to predict the influence of age, duration of diabetes, race, insurance status, and insulin administration on glycemic outcomes. Regression analysis revealed significant equations for all glycemic outcomes, demonstrating a strong correlation (p<0.0001, p=0.0001, and p<0.0001, respectively). However, after controlling for these variables, only race and duration of diabetes remained independently associated with glycemic outcomes, suggesting that these factors strongly influence glycemic control independent of age, sex, insurance, and pump use. Conclusion. Even in a subset of youth with T1D using CGM with high rates of insulin pump use, disparities in glycemic outcomes persist. When evaluating glycemic outcomes, race remained a significant cofactor despite controlling for age, duration of diabetes, sex, insurance status, and insulin administration type. These results add to the existing literature, and demonstrate race remains strong predictor of glycemic outcomes.